iant extradural dermoid cyst in the right parietal-occipital region with obliteration of the transverse sinus - K. A. Belozerskikh; G. Yu. Evzikov (Опухоли головы и шеи, 2021)
The study objective – to report a case of giant extradural dermoid cyst in a 48‑year-old woman; the cyst caused extensive erosion of the occipital bone and lower portions of the right parietal bone, which is quite rare.Case report. A 48‑year-old female patient was admitted to the Department of Neurosurgery, A. Ya. Kozhevnikov Clinic of Nervous System Diseases, University Clinical Hospital No. 3, I. M . Sechenov First Moscow State Medical University on 28.07.2020. In 2002, the patient noted the emergence of a 1‑cm subcutaneous formation in the right occipital region. The formation was slowly growing. On 17.12.2015, she underwent magnetic resonance imaging of the brain. It revealed a 2,5 × 4,4 × 4,0 cm extradural formation with clear contours and erosion of the occipital and right parietal bones. On 12.03.2020, she had contrast-enhanced magnetic resonance imaging, which demonstrated that the tumor was growing (its size was 3,0 × 6,4 × 5,5 cm). Magnetic resonance imaging scans also showed extensive erosion (6,4 × 5,4 cm) of the occipital and right parietal bones and obliteration of the right transverse sinus. On 28.07.2020, the patient underwent elective surgery, namely excision of the extradural dermoid cyst in the right parietooccipital region with simultaneous reconstruction of the calvarial bones using a titanium plate. The cyst capsule and its contents were completely removed. The capsule was tightly attached to the dura mater, but did not invade it. To remove small fragments of the capsule that could potentially invade the bone, we performed small marginal resection of the calvarial bones at the depth of 2–3 mm from the defect margin. After the removal of cyst capsule, well-defined furrow could be visualized on the dura mater in the projection of the obliterated transverse sinus. Five days postoperatively, the patient was discharged from hospital in satisfactory condition.Conclusion. Surgical treatment of extradural dermoid cysts implies radical removal of the tumor. Since the cyst capsule gets tightly attached to the edges of the bone defect along with bone erosion, the removal of such cysts as a single block is almost impossible. The risk of severe erosion of the skull bones caused by a dermoid cyst with extradural (and sometimes intradural) growth increases with age. Therefore, it is recommended to remove such tumors as early as possible. Patients with skull bone defects also require cranioplasty.